Farmers’ Willingness to Continue Corporate Farming Programs in Jetis Subdistrict, Bantul Regency, Yogyakarta - Putri Perdana; Jamhari Jamhari; Irham Irham (Agro Ekonomi, 2020)
Corporate Farming (CF) program is one of the innovations in the field of agricultural institution in realizing more effective and efficient farming through consolidation of paddy field. This program was carried out in Trimulyo Village, Jetis Sub-district, Bantul Regency with Barokah Farmers Group as a pilot project. This study aimed to (1) determine farmers’ willingness to continue the CF program and (2) determine the factors that affect farmers’ willingness to continue the CF program. The study was conducted by surveying 52 smallholder farmers, members of Barokah Farmers Group who joined the CF program. The data were analyzed by using proportion test and Ordinary Least Square (OLS) model. The results showed that the farmers' willingness to continue the CF program was 66.54%. Attitudes towards private property rights, interaction among the members of farmer group, family member support, age and education were the factors that affect farmers' willingness to continue the CF programs. Farmers’ willingness to continue the CF program was categorized as high. Socialization and a more intense mentoring on the objectives of the CF program can increase farmers' willingness to continue the program.